2014
DOI: 10.1021/nn5062657
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Intracellular Self-Assembly and Disassembly of 19F Nanoparticles for MR Imaging of Caspase 3/7 in Zebrafish

Abstract: Compared to (1)H MRI, (19)F MRI provides higher selectivity but lower sensitivity. Therefore, the need to inject high doses of the (19)F probe to improve its sensitivity for in vivo diagnosis remains a challenge. A "smart" strategy is needed that could locally concentrate a low-dose (19)F probe while avoiding the fast transverse relaxation of the probes. Locally self-assembling and disassembling (19)F nanoparticles may be an optimal measure to achieve this goal. Herein, we report a dual-functional probe 1 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 34 publications
0
96
0
Order By: Relevance
“…In general, such reports have used pre-existing MRI coils that are not tailored to the species, including the use of expensive cryogenic coils to boost signal reception. Many of these previous studies have been performed using ex vivo or fixed fish [26], [27], [28] as opposed to our system that uses live subjects with full recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In general, such reports have used pre-existing MRI coils that are not tailored to the species, including the use of expensive cryogenic coils to boost signal reception. Many of these previous studies have been performed using ex vivo or fixed fish [26], [27], [28] as opposed to our system that uses live subjects with full recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the therapeutic self-monitoring could be achieved simultaneously to further enhance the anticancer efficacy 23-25. Given the critical roles of caspase-3 in cell-death process, various caspase-3 activatable imaging reagents 26, including 19 F magnetic resonance imaging probe 27, positron emission tomography tracer 28, quantum dot sensor 29 and fluorescence probe 30, have been developed for reporting the apoptotic information. These approaches offer good opportunity to easily investigate treatment-to-effect correlations.…”
Section: Introductionmentioning
confidence: 99%
“…11, 14 In this case, we demonstrated that 19 F NMR signal can be turned on by tuning the particle size and shape by either breaking the coplanarity or improving the hydrophilicity. Therefore, it is crucial to take selfassembly into consideration during the design of novel amphiphilic 19 F MRI agents.…”
Section: Scheme 1 Synthesis Of Amphiphiles 1 8 and 11mentioning
confidence: 77%